Lymphatic Contribution to the Cellular Niche in Heterotopic Ossification. Issue 6 (December 2016) - Loder, Shawn; Agarwal, Shailesh; Sorkin, Michael; Breuler, Chris; Li, John; Peterson, Joshua; Gardenier, Jason; Hsieh, Hsiao Hsin Sung; Wang, Stewart C.; Mehrara, Babak J.; Levi, Benjamin
Abstract : Objective: The objective of this study was to determine the contribution of lymphatic tissue to heterotopic ossification (HO). Background: HO is the pathologic development of ectopic bone within soft tissues often following severe trauma. Characterization of the tissue niche supporting HO is critical to identifying therapies directed against this condition. Lymphangiogenesis is upregulated during incidents of trauma, thereby coincident with the niche supportive of HO. We hypothesized that lymphatic tissues play a critical role in HO formation. Methods: Mice underwent hindlimb Achilles' tendon transection and dorsal burn injury (burn/tenotomy) to induce HO. The popliteal and inguinal lymph nodes were excised ipsilateral to the tenotomy site. Flow cytometry and immunostaining were used to quantify and localize lymphoendothelium. MicroCT was used to quantify HO. Results: Enrichment of mature lymphatic tissues was noted 2 weeks after injury at the tendon transection sites when compared with the contralateral, intact tendon based on LYVE1+ tubules (10.9% vs 0.8%, P < 0.05). Excision of the inguinal and popliteal nodes with draining popliteal lymphatic vessel significantly decreased the presence of mature lymphoendothelium 2 weeks after injury (10.9% vs 3.3%, P < 0.05). Bone-cartilage-stromal progenitor cells (CD105+/AlphaV+/Tie2-/CD45-/CD90-/BP1-) were also significantly decreased after lymph node excision (10.2% vs 0.5%, P < 0.05). A significant decrease was noted in the volume of de novo HO present within the soft tissues (0.12 mm 3 vs 0.02 mm 3 ). Conclusion: These findings suggest that lymphatic vessels are intimately linked with the de novo formation bone within soft tissues following trauma, and their presence may facilitate bone formation. Abstract : Supplemental Digital Content is available in the text